Nanomaterials: Full Gamut Wall Tunability from Persistent Micelle Templates via Ex Situ Hydrolysis (Small 18/2019). Issue 18 (3rd May 2019) - Lantz, Kayla A.; Clamp, Nicholas Blake; van den Bergh, Wessel; Sarkar, Amrita; Stefik, Morgan
Abstract : In article number1900393, Morgan Stefik and co‐workers improve a micelle template strategy to decouple micelle control from reactive material additions. The series of porous TiO2 materials exhibit tunable confinement effects upon electrochemical lithiation. Analogous to a vending machine, this materials by design approach yields tunable sample libraries and supports nano‐optimization. The Authors thank Jacob Wade Marsh for the graphic design.